Obtenção, caracterização e avaliação da performance fotocatalítica de nanoestruturas de TiO2 contendo metais de transição (Nb e W) - Santos, Emerson Chaves dos (2022)
Heterogeneous photocatalysis has been considered a promising alternative for the removal of several organic pollutants linked to environmental pollution. Among a range of materials currently used, titanium dioxide (TiO2), especially in the anatase phase, it stands out for presenting intrinsic characteristics appropriate for a photocatalyst, such as high stability, photoactivity, atoxicity, and others. As a result, it was has been established that the photocatalytic efficiency of TiO2 is related to several characteristics such as size, shape, crystalline structure, presence of dopants, and others. Thus, the main objective of this work was to obtain, characterize and evaluate the effects of the addition of metallic ions as Tungsten (W) and Niobium (Nb) on the photocatalytic properties of TiO2 nanostructures. These nanostructures were prepared using the conventional hydrothermal method, without the use of additives such as surfactants or halides, at the temperature equal to 200 ºC. The analyzes carried out through the experimental techniques such as X-ray diffraction (XRD) and Raman spectroscopy showed that all samples presented the anatase crystalline phase, regardless of the type or amount of metal ions. The Electron microscopy measurements confirmed the change in morphology as a function of the amount of metallic ions, but are not in relation to the type, W or Nb. The photocatalytic performance of the samples obtained has been evaluated in the degradation of Rhodamine B (Rod.B) and Methylene Blue (AM) dyes, photoactivated by exposure to ultraviolet radiation. According to photocatalytic assays and XPS results, the MxTi1−xO2 (M = Nb and W) nanostructures obtained had their surface characteristics has been altered, favoring the degradation of cationic dyes such as AM. Thus, the Raman and XPS results showed that the amount of metallic ions induced an increase in the presence of defects in the structure, which brought a deleterious effect to the degradation of the Rod.B dye. In a final step, the proposed method also presented promising results concerning to obtaining doped nanostructures only with N (TiO2N) and co-doped nanostructures (W0.03Ti0.97O2N, W0.29Ti0.71O2N, Nb0.02Ti0.98O2N and Nb0.27Ti0.73O2N). The co-doped samples has showed higher photocatalytic performance compared to samples containing only the presence of metal ions, since the results suggest that the presence of N favored the formation of defect pairs, consequently reducing the rate of recombination of charge carriers.